The role of cybersecurity in reducing the number of cybercrimes In Aqaba Governorate "Using geographic information systems" - Al-Anouz, Suzan Muhammad Saleh (Journal of Humanities & Social Sciences, 2024)
The study aims to clarify the difference between cybersecurity and information security, and their relationship to the increase or decrease in electronic crimes, through geographical information systems programs that help in knowing the color gradation in the percentage of increase or decrease in electronic crimes, as the dark color indicates the highest percentage, and the light color indicates the lowest. percentage during the study period. Geographic information systems study the areas of information technology based on the spatial analysis approach and digital maps. The study relies on the descriptive, analytical, and historical approach, to arrive at the most important results and solutions that limit cybercrimes that a person does not realize how dangerous they are to him. This study also seeks to identify the most important cybercrimes, their objectives, and their relationship to cybersecurity (cybercrimes), and clarify the extent of their effects and how to prevent them. The study ended with a conclusion that includes the results and recommendations.